Exertional collapse in the runner: Evaluation and management in fieldside and office-based settings - Childress, M. A.; O'Connor, F. G.; Levine, B. D. (Clinics in Sports Medicine, 2010)
Exertional collapse is a commonly encountered phenomenon among runners, particularly in the setting of long distances and extreme environments. Although exertional collapse is generally a benign event occurring in an exhausted finisher at race completion, the multifactorial nature of this disorder creates a broad differential diagnosis. The ability of the sports provider to appropriately recognize and treat these various potential concerns is critical, because collapse may represent several life-threatening conditions. It is especially challenging to determine the appropriate course of evaluation and management of collapse in the context of a mass participation event. This article presents a discussion of the etiology and pathophysiology of collapse as well as strategies for the effective assessment and treatment of collapsed runners, whether in the fieldside setting or in an outpatient office-based environment.